Analisis Pengaruh Tingkat Pertumbuhan Ekonomi Dan Tingkat Pengangguran Terhadap Tingkat Kemiskinan Di Kabupaten/Kota Kulonprogo, Bantul, Gunung Kidul, Sleman, Dan Yogyakarta - Meti Astuti; Indri Lestari (At-Tauzi : Jurnal Ekonomi Islam, 2018)
This research aims to analyze the effect of economic growth, unemployment rate on the poverty rate in regency/city Kulonprogo, Bantul, Gunung Kidul, Sleman and Yogyakarta, research of year 2013- 2016. The analytical method used in this study is multiple regression analysis .The results show that Economic growth in Kulonprogo, Bantul, GunungKidul is positifely and no significan effect on the poverty rate, and Sleman, Yogyakarta is negatively and no significan effect on the poverty rate. Where, unemployment rate in Kulonprogo, Bantul, GunungKidul, Yogyakarta is positifely effect on the poverty rate and Sleman is negatively no significan effect on the poverty rate.